Model Identification for Flow Simulations in Geothermal Reservoirs: Towards Optimally Drilling Boreholes. Issue 1 (December 2013) - Padalkina, Kateryna; Bücker, H. Martin; Herty, Michael; Rath, Volker; Seidler, Ralf
Abstract In geothermal reservoir engineering, one is interested in determining the location of boreholes such that measurements taken therein, say temperature, will allow the estimation of unknown parameters such as porosity and permeability. We formulate such a particular borehole location problem and find its solution by techniques from optimal experimental design. More precisely, we minimize the D‐optimality criterion to find an optimal location of a single borehole to estimate hydraulic permeability from temperature measurements in two boreholes. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)